Sleep Outcomes With Cognitive Behavioral Therapy for Insomnia Are Similar Between Older Adults With Low vs. High Self-Reported Physical Activity - Yeung, Timothy; Martin, Jennifer L.; Fung, Constance H.; Fiorentino, Lavinia; Dzierzewski, Joseph M.; Rodriguez Tapia, Juan C.; Song, Yeonsu; Josephson, Karen; Jouldjian, Stella; Mitchell, Michael N.; Alessi, Cathy (Frontiers in Aging Neuroscience, 2018)
We examined whether baseline physical activity is associated with the efficacy of cognitive behavioral therapy for insomnia (CBT-I) in older veterans. Community-dwelling veterans aged 60 years and older with insomnia received CBT-I in a randomized controlled trial. Participants who received active treatment were divided into low and high physical activity based on self-report. Sleep outcomes were measured by sleep diary, questionnaire, and wrist actigraphy; collected at baseline, post-treatment, 6-months, and 12-months follow-up. Mixed-effects models compared differences between physical activity groups in change in sleep outcome from baseline to each follow-up, and equivalence tests examined if physical activity groups were clinically equal. There were no significant differences in sleep outcomes between physical activity groups. Equivalence tests suggested possible equality in physical activity groups for five of seven sleep outcomes. Efficacy of CBT-I in older veterans was not associated with physical activity. Older adults with low levels of physical activity who have insomnia can benefit from CBT-I.